1983
DOI: 10.3109/00016358309162311
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Healing of Replanted Monkey Teeth Prevented from Drying

Abstract: Root resorption of replanted teeth is dependent on the duration of the extra-alveolar period and on the storage environment. In the present investigation the significance of preserving the humidity of the periodontal ligament (PDL) during the extra-alveolar period was tested on isolated PDL cells and on replanted monkey teeth. The isolated PDL cells were tested with respect to cell viability (trypan blue exclusion test) and to cell recovery (number of cells after additional cultivation). About 70% of the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1
10

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 12 publications
8
87
1
10
Order By: Relevance
“…For up to an hour the vitality of the cement can be maintained by wrapping the tooth in plastic foil. 3 For longer than that cell viability can be sustained by storing the tooth in milk, which has an osmolarity and pH (230-270 mmol/kg and 6 6) compatible with cell survival. 4 Reimplantation is carried out by rinsing the tooth gently in saline and placing it in the socket, taking care to handle it by the crown.…”
Section: Emergency Treatment Of Avulsed Incisor Teethmentioning
confidence: 99%
“…For up to an hour the vitality of the cement can be maintained by wrapping the tooth in plastic foil. 3 For longer than that cell viability can be sustained by storing the tooth in milk, which has an osmolarity and pH (230-270 mmol/kg and 6 6) compatible with cell survival. 4 Reimplantation is carried out by rinsing the tooth gently in saline and placing it in the socket, taking care to handle it by the crown.…”
Section: Emergency Treatment Of Avulsed Incisor Teethmentioning
confidence: 99%
“…Posteriormente, el conducto fue obturado con un apósito de hidróxido de calcio en pasta, Calcifar -P (Eufar ® ) (Figura 2 y 3). [21][22][23][24][25][26][27][28][29][30][31][32][33] Figura 2. Estimación de la longitud de trabajo en 20 mm.…”
Section: Tratamiento Del Conducto Radicularunclassified
“…Blomlof et al (1983) Pre-Replantation Contamination Lindskog and Blomlof (1982) noted the adherence of bacteria to the surface membrane of PL cells stored in saliva. This is important because of the lytic effect of bacterial enzymes and toxins (Lindskog and Blomlof 1982 …”
Section: Pre-replantation Duration and Storaaementioning
confidence: 99%
“…After 120 minutes of desiccation, no viable cells remain on the root surface (Soder et al 1977; Lekic et al 1998). A histological outcome study of lateral incisors from 8 monkeys suggested that 30-40 minutes rnay be the b i t of drying to avoid severe root resorption as early as 8 weeks after replantation (Blomlof et al 1983). …”
Section: Pre-replantation Duration and Storaaementioning
confidence: 99%